ANALISIS FAKTOR KELELAHAN KERJA DENGAN METODE CHI-SQUARE PADA SISTEM KERJA LONGSHIFT OPERATOR HD SANY SKT80S : ANALYSIS OF WORK FATIGUE ON LONGSHIFT WORKING TIME BY HD SANY SKT80S OPERATOR USING CHI-SQUARE METHOD - Nurhidayat, Muh.; Abigani, Rahfa; Virgiyanti, Lisa; Murati, Ferra; Nomeritae, Nomeritae (JURUSAN TEKNIK PERTAMBANGAN UPR, 2023)
Activities of coal mining at PT Mitra Barito Lumbung Energi's use a long-shift work system. Thus, can lead to a very high levels of risk exhaustion. Purpose of this study was to determine the effect of longshift on the work fatigue of HD Sany SKT80S operators by using the Work Fatigue Measurement Tool Questionnaire (KAUPK2). This study uses the relationship parameter between age and body mass index. The method used in this study is a statistical test method, namely the Chi-Square Test (Fisher's Exact Test), with data analysis using bivariate. The sampling technique used was judgment sampling with 14 respondents. The results showed that 8 out of 14 HD Sany SKT80S operators felt a relationship between work fatigue and the age factor, with symptoms of a sore right or left shoulder. The perception of fatigue is already above 50% that concluded that there are fatigue experienced by HD Sany SKT80S operators. Then, of the 20 dependent factors tested with two independent factors, the result is that the body mass index has no relationship with symptoms of work fatigue, but the age factor has a relationship with symptoms of work fatigue in its tested operators. Keywords : Longshift, the Work Fatigue Measurement Tool Questionnaire (KAUPK2), fatique